Deciphering the microRNA signature of pathological cardiac hypertrophy by engineered heart tissue- and sequencing-technology. (April 2015) - Hirt, Marc N.; Werner, Tessa; Indenbirken, Daniela; Alawi, Malik; Demin, Paul; Kunze, Ann-Cathrin; Stenzig, Justus; Starbatty, Jutta; Hansen, Arne; Fiedler, Jan; Thum, Thomas; Eschenhagen, Thomas
Abstract: Pathological cardiac hypertrophy and fibrosis are modulated by a set of microRNAs, most of which have been detected in biologically complex animal models of hypertrophy by arrays with moderate sensitivity and disregard of passenger strand (previously "star") microRNAs. Here, we aimed at precisely analyzing the microRNA signature of cardiac hypertrophy and fibrosis by RNA sequencing in a standardized in vitro hypertrophy model based on engineered heart tissue (EHT). Spontaneously beating, force-generating fibrin EHTs from neonatal rat heart cells were subjected to afterload enhancement for 7 days (AE-EHT), and EHTs without intervention served as controls. AE resulted in reduced contractile force and relaxation velocity, fibrotic changes and reactivation of the fetal gene program. Small RNAs were extracted from control and AE-EHTs and sequencing yielded almost 750 different mature microRNAs, many of which have never been described before in rats. The detection of both arms of the precursor stem–loop (pre-miRNA), namely -3p and -5p miRs, was frequent. 22 abundantly sequenced microRNAs were > 1.3 × upregulated and 15 abundantly sequenced microRNAs downregulated to < 0.77 ×. Among the upregulated microRNAs were 3 pairs of guide and passenger strand microRNAs (miR-21-5p/-3p, miR-322-5p/-3p, miR-210-3p/-5p) and one single passenger strand microRNA (miR-140-3p). Among downregulated microRNAs were 3 pairs (miR-133a-3p/-5p, miR-30e-5p/3p, miR-30c-5p/-3p). Preincubating EHTs with anti-miR-21-5p markedly attenuated the AE-induced contractile failure, cardiomyocyte hypertrophy and fibrotic response, recapitulating prior results in whole animals. Taken together, AE-induced pathological hypertrophy in EHTs is associated with 37 differentially regulated microRNAs, including many passenger strands. Antagonizing miR-21-5p ameliorates dysfunction in this model. Highlights: Hypertrophied engineered heart tissue shows a distinct miRNA signature by RNA-seq. Many of a total of 750 miRNAs have not been described in rats before. Hypertrophy-regulated miRNAs in vitro are a subfraction of TAC-regulated miRNAs. Inhibition of miR-21-5p during hypertrophic intervention improved EHT function. Fibrotic changes and cardiomyocyte hypertrophy were attenuated by anti-miR-21-5p.